Factors Influencing Repurchase Decisions in the Service Industry in Lombok, West Nusa Tenggara - Tahsim Tahsim; Ridwan Basalamah; Siti Aisyah (Jurnal Bisnis dan Manajemen, 2023)
The realization of customer repeat purchases will have a positive impact on the company because customers will continue to use the product for a long time. Therefore, this study aims to determine and analyze the effect of service quality and promotion on purchasing decisions with consumer satisfaction as the mediator. This study used quantitative analysis with the partial least squares structural equation model approach (SEM-PLS). Data collection was carried out using a questionnaire on Magenta English Course students. The distribution of the questionnaire was carried out via the google form and successfully responded to 106 students using a purposive sampling technique. Respondents were spread across all December 2022 course participants and alumni who had taken courses at the Magenta English Course. The sample is sufficient to represent the entire population of Magenta English Course students. The number of samples is obtained from calculations using the Slovin formula with a probability of 5%. Data were analyzed using SmartPLs 3.0. The results of this study indicate that service quality has no effect on repurchasing decisions. However, service quality affects consumer satisfaction. Then promotion has a significant effect on repurchasing decisions. Promotion has a significant effect on consumer satisfaction, as well as customer satisfaction which has a significant effect on increasing repurchase decisions. Finally, customer satisfaction becomes a mediating variable between promotion and repurchase decisions.